Service-learning Outcomes Measurement Scale (S-LOMS): Chinese Translation and Validation - Lau, Ka Hing; Snell, Robin Stanley; Keung, Jeffrey Ching To (Silliman Journal, 2022)
The Service-Learning Outcomes Measurement Scale (S-LOMS) was developed in Hong Kong and established as a valid and reliable instrument. It is a resource for further advancing service-learning in Hong Kong and potentially across Asia. Since Chinese-speaking regions comprise a major proportion of the population of Asia, the first translation project for S-LOMS was from English into Chinese. This study reports how this was done and how the Chinese version was validated. The Chinese S-LOMS was developed using a back-translation approach and then pre-tested with 11 students, who were interviewed about their understanding of the constituent items. The pre-testing results suggested that the Chinese S-LOMS has good translation validity, equivalent to that of the original English version. An empirical validation exercise with a sample of 106 participants from a Hong Kong local secondary school was conducted with factor analysis and reliability checking. Results indicated good validity and internal consistency